IMPLEMENTATION OF CHARACTER EDUCATION THROUGH SCHOOL CULTURE AT MTS NW SELEBUNG, KERUAK DISTRICT, EAST LOMBOK REGENCY - Aswanti (Formad English Foundation NTB Jakarta, 2024)
Character education is a crucial aspect of developing moral values among students. This study explores the implementation of character education through school culture at MTs NW Selebung, focusing on elements such as social care, nationalism, discipline, and hard work. The research employed a qualitative approach, utilizing interviews, observations, and document analysis to gather data. The findings reveal that the school's commitment to social care, through community support activities, and the promotion of nationalism, demonstrated through flag ceremonies and competitions, play a vital role in shaping students' character. Additionally, a disciplined environment fosters adherence to school rules, reinforcing positive behaviors. The study concludes that integrating character education into daily school activities significantly enhances students' moral and social competencies. These insights contribute to the existing literature on character education and offer practical implications for educational institutions seeking to cultivate a strong moral foundation among students. Future research should consider broader sample sizes and diverse educational contexts to deepen understanding of effective character education practices.